Error Analysis on English Translation from Indonesian on Public Facilities in Semarang City - Ayu Ida Savitri (Universitas Dian Nuswantoro, 2019)
Delivering exactly and accurately the same message of a text under minor bias and without any form and meaning shifts in another language has always becoming the final-purpose of a translation process as the main objective of translation is transferring the message of a text in one language into another one by highly considering on how the readers of another language will understand and enjoy the translation while obtaining the needed information. Most of the time, the difficulties of expressing similar message in another language lays on the different interpretation due to the different culture. To deal with it, a translator must be a ‘balance-bilingualist’ as she/he must understand well the languages involved in the translation process. Sometimes, the error in translation occurs when the structure of the first language/the source language (SL) of the translator influence the translation in second language/ target language (TL). To analyse the error, Error Analysis Theory from Richard (1974) and Types of Error in producing English from Dulay (1982) is used as it is aimed at revealing the kinds or error along with the factors influencing the error. This research is done to describe the error in public translation such as billboard, banner and decoration containing wise words around Semarang City to show the kinds of error and the factors influencing those errors along with the way the translator translate the text under Translation Theory from Catford (1965) and Nida and Taber (1969) also Translation Model from Venuti (2000) and Translation Method and Technique/ Procedure from Vinay and Darbelnet (1958). The result shows that most of the errors are in generalization that happened as a result of the influence of the first language/SL structure and writing system that is different with that of the second language/TL.